ANALYSIS OF BEHAVIORAL DEVIATIONS IN CHILDREN OF HIGH SCHOOL AGE - Mavianti Mavianti (Proceeding International Seminar of Islamic Studies, 2022)
This research was conducted among high school students, where deviations are rife. The problems studied are how these deviations can occur, the forms of deviations carried out and how the efforts of the school and parents to deal with them. The theories used for this research are deviation theory, social action theory, and also social control theory. The researcher uses a descriptive qualitative research method where the focus of this research is the phenomena that occur in the field according to the actual situation by solving problems as they are. From the results of this study, the type of deviation that is mostly done is at the high school level, where in this phase teenagers spend a lot of time outside the home to find new experiences so that there is an unfavorable relationship between parents and children. The lack of the role of the school also affects the process of this deviation. The forms of deviations that occur also vary, ranging from the lowest level to the highest level. Deviations made this happen can be influenced by the playing environment or even from the closest family itself. Teenagers who commit these deviations are often not aware of what they have done. Therefore, the role of parents as an internal factor is needed to educate children to be more aware of the form of the deviation itself. The school as an external factor is no less important for educating children who are in the adolescent phase. The deviations that occur have also reached a reasonable limit, due to the development of the times and also the unfavorable environment. In this study, researchers tried to find efforts that can be made by parents and also the school to reduce this deviation.